A Systematic Review of the Aspects and Benefits Agile Project Management Innovation - Fidyawan, Miftahul Agtamas; Raharjo, Teguh (AI Society & STMIK Indonesia, 2023)
Agile Project Management (APM) has developed throughout industries for years. Many companies chose APM for their initiatives. APM has been shown to help those who use it. Many APM adopters innovated and tailored the methodology. Innovation improved project agility. Innovation includes life cycle and development approach selection, processes, involvement, tools, methodologies, and artifacts. This study performed a Kitchenham-based systematic literature review in three steps: planning, conducting, and reporting systematic review. The 23 articles were chosen from ACM Digital Library, EBSCOhost, IEEE Xplore, Sage Journals, ScienceDirect, and Semantic Scholar. Journal articles or conference papers were possible. The findings of this study showed that PMBOK 7th Edition could map all previous studies into related innovation aspects. Then, the review demonstrated that each innovation improved the PMBOK 7th Edition performance domain. Finally, this study showed that organization-driven innovation could benefit the organization.